The comprasion of prevalance, type and severity of injury in professional and amateur freestyles' wrestlers - Ali Belfani; Eynollah Naderi; Mehrdad Anbarian; Abbas Baglarbagi (Vesnu Publications, 2013)
Abstract Introduction:Researchers make an effort to the assessment of injuries prevalence in different sports, to the find the cause of this injury and eventually to provide the appropriate prevention strategies. But yet have observed a lot of injures and remained unclear patterns of sport injury in athletes of different sports disciplines. This study has compared the incidence, type and severity of acute injury in professional and amateur freestyles' wrestlers. Materials and Methods: The research subjects included twenty eight professional wrestlers that selected in the targeted method and twenty matched amateur wrestlers that chosen with the randomized method in Hamadan, Kermanshah, and Kurdistan cities. Data collection tool was a questionnaire that was developed by the researcher and was confirmed by sport medicine experts. All subjects signed the consent form before entering to study. The questionnaire was completed by the wrestlers to assess the incidence, mechanism, type and severity of acute injury in the professional and amateur freestyles' wrestlers in past one year. Collected data were analyzed by SPSS software, version 16, and descriptive and inferential statistical methods of chi square test in the significant level of P< 0/05. Results: The findings showed that there are significant differences only between the type of injury in the amateur and professional freestyles' wrestlers (p=0/019), severe injures proportion in both groups were the most and injury incidence during wrestle specific training was the most (amateur 70.3% and professional wrestlers 64.3%). The most common mechanism of injury was reported opponent's error (30.0%) for the professional wrestlers, lack of physical fitness (37/8%) and opponent's error (31/1%) were reported for the amateur wrestlers. The head- face- neck, shoulder and knee injuries were the most susceptible areas in both groups. Conclusion: However, there was an assumption that professional and amateur wrestler, since of the different levels of physical fitness, equipment and experience in the amateur and professional levels, is different in the extent of the injury but not so. Therefore to have a definitive discretion, research on the broader level is needed. Keywords:freestyle wrestling, wrestling, sports injury